A comprehensive review of dwell time optimization methods in computer-controlled optical surfacing - Tianyi Wang; Xiaolong Ke; Lei Huang; Qingqing Cui; Zili Zhang; Chunjin Wang; Hyukmo Kang; Weslin Pullen; Heejoo Choi; Daewook Kim; Vipender Negi; Qian Kemao; et al. (Light: Advanced Manufacturing)
Dwell time plays a vital role in determining the accuracy and convergence of the computer-controlled optical surfacing process. However, optimizing dwell time presents a challenge due to its ill-posed nature, resulting in non-unique solutions. To address this issue, several well-known methods have emerged, including the iterative, Bayesian, Fourier transform, and matrix-form methods. Despite their independent development, these methods share common objectives, such as minimizing residual errors, ensuring dwell time's positivity and smoothness, minimizing total processing time, and enabling flexible dwell positions. This paper aims to comprehensively review the existing dwell time optimization methods, explore their interrelationships, provide insights for their effective implementations, evaluate their performances, and ultimately propose a unified dwell time optimization methodology.